Coulometric sizing of nanoparticles: Cathodic and anodic impact experiments open two independent routes to electrochemical sizing of Fe3O4 nanoparticles - Tschulik, K; Haddou, B; Omanović, D; Rees, N; Compton, R (2013)
Anodic particle coulometry (APC) is a recently established method of sizing individual metal nanoparticles by oxidising them during their impact on a micro electrode. Here it is demonstrated that the application of APC can be extended to sizing of metal oxide nanoparticles, such as Fe3O4 magnetite nanoparticles. Additionally, a new route to electrochemical nanoparticle sizing is introduced-cathodic particle coulometry (CPC). This method uses the reduction of impacting nanoparticles, e.g., metal oxide nanoparticles, and is demonstrated to yield correct size information for Fe3O4 nanoparticles. The combination of these two independent electrochemical methods of nanoparticle sizing, allows for purely electrochemical sizing of single nanoparticles and simultaneous verification of the obtained results. © 2013 Tsinghua University Press and Springer-Verlag Berlin Heidelberg.